Optimalisasi penataan untuk peningkatan Sense Of Place pada Kawasan Jembatan Nagit Marisa - Nurmiah Nurmiah; Moh. Eran (Universitas Muslim Indonesia, 2022)
the existence of the Nagit Bridge bridge in the surrounding residential area has a sense of place decline, this makes the level of urgency in its management. The residential area under the Nagit Bridge on the banks of the Marisa river which has positive potential in the form of a strategic location in its orientation to other locations, and environmental exoticism. in the arrangement and effect of the existence of the Nagit bridge which is the circulation path for the creation of Space Communication to create a Sense of Place. The purpose of this study is to determine the effectiveness of the existing space in the Regional Space under the Nagit Marisa Bridge which has experienced a decrease in effectiveness due to a lack of sense of space. This study uses a qualitative method by emphasizing the problems that occur in the field based on realistic conditions and exploring the existing reality in the form of a description of the results of observational analysis and an understanding of the information obtained. The results of the research obtained Optimization of increasing the sense of place in the Nagit bridge area can be optimized on the factors of 3 main factors, namely the mass arrangement of the second building for Pedestrians in an area, the third function of space in open space, the potential for interesting views around the bridge can strengthen the sense of an area in the Nagit bridge area, the main building is covered by additional buildings, the arrangement of the height and setback of the serial view building and one of the concepts applied is how the height of the building or skyline to the bridge, the integration between visual elements of circulation and street furniture is located on the shoulder of the road without any dominance. public environment. non-permanent activity dewatering paths that need to be accommodated in the design and integrity of vegetation in open spaces.